CODESRIA Bulletin Online, No. 2, January 2021: Olabiyi Babalola J. Yai (1939–2020): An Iroko Joins the Ancestors - Sanya Osha (CODESRIA Bulletin, 2021)
I met Professor Abiola Francis Irele at a conference hosted by the Institute for Pan-African Thought and Conversation (IPTC) in Johannesburg a couple of months before he passed away in 2017. Throughout the huge conference, I sought several opportunities to be by Irele’s side, ravenously tapping into his wealth of knowledge and experience, plying him with an endless barrage of questions relating to our intellectual history and the key figures who had indelibly marked and shaped its trajectory. The esteemed professor, ever so patient, was ready to respond to even the most uncomfortable of entreaties. He possessed the unflappable sangfroid of a sage, yet there was nothing inaccessible about his almost earthy aura. He was unfailingly modest and never condescending to me even when he had ample reason to do so. He passed away within three months of returning to Harvard in the United States where he had been based for a considerable period before returning to Nigeria to support the development of Kwara State University as the inaugural Provost of the College of Humanities, Management and Social Sciences. I was informed of the news by his dear friend, Professor Olabiyi Babalola Yai, who was clearly distraught when he declared he had lost his brother. As Yai expressed the great loss, one felt his heart had been ripped out leaving behind a gaping void. At the conference, Irele and I had discussed Yai’s work. When I brought up the issue, Irele uncharacteristically could not find the exact words to capture the essence of Yai’s oeuvre. He had sort of winced, indicating by making carving gestures with his hands, that Yai worked like a fastidious sculptor of words. Yai’s writing, in other words, was an exercise in textural sculpture, akin to a furnace of skewed intellectual contestation, and a work of unyielding scribal architecture. If rough, uneven and perhaps sometimes imprecise on the surface, it was an imprecision that seemed deliberate, forged in the hardened crucible of character formation, with the range and sturdiness of mountain rocks or the blasted rigour of gnarled ancient trees. That is what I had read in Irele’s wince and gestures in relation to the unique work of Professor Olabiyi Yai. When Abiola Irele passed, I felt lost, bereft of thought and words, perhaps even of feeling. I just couldn’t bring myself to pen a tribute as simple as that. After-all, even if it seemed I had known him throughout my career, I had only met him in person four times. Twice at Ibadan, Nigeria in 1991 and 2001 and once in Pietermaritzburg in the Kwazulu-Natal province of South Africa at a literature conference in 2004. The final time was in Johannesburg. Yet, as I mentioned, it seemed I had known him all my life and in a way I had. His younger brother Professor Oladipo Irele had been my teacher, mentor and older brother long before I met the elder Irele. I had been seasoned by tales of the elder Irele’s legendary brilliance and stature in African literary history. Irele had been my editor on three landmark platforms. The first being the journal, Research in African Literatures (based at Ohio State University), the Oxford Encyclopedia of African Thought project, which he co-edited with Professor Biodun Jeyifo and the third platform was the Harvard-based journal, Transition. Remotely, Irele had guided my scholarly development without needing to do so in the explicit or formal sense of the term. But each of my pieces of work submitted to his editorial guidance had been a necessary and important journey. In other words, a pilgrimage of self-discovery and self-realisation. His particular style of instruction lacked any intrusive character at first glance. He could be simply compelling in the way he sent you off on a voyage of self-knowledge in which you had to discover how to swim, or alternately, to fall on your own sword. Either way, you shall discover truths that you never previously recognised about yourself. I remember in 2005 when a Finnish editor came to me at a Cape Town conference to solicit a paper on sexuality for his journal. I sent him an essay I had written on Sarah Baartman, exploring the nexus between race, infrahumanity and sexuality. Subsequently, I received the most damaging of reviews in my entire career. The reviewers had been so scathing in their criticisms that the ordinary response would have been to give up writing altogether. But then I remembered the counsel of the late formidable Moshood K.O. Abiola, the presumed winner of the watershed June 12, 1993 presidential elections in Nigeria, who had said that when one is stricken by disaster, we ought to look for an even greater catastrophe to mitigate the blow of the earlier one. And so I decided to send off the roundly rejected essay to Transition with the hope that I would receive an even more brutal batch of reviews. Afterall, Transition is unique in having two Nobel prize winners on its editorial board at the same time, the late Toni Morrison and our own Wole Soyinka, and had attained mythic status by having sprung the fecund heart of East African intellectual thought, reached the peppery and tropical shores of West Africa, before finally alighting in America where it now boldly looks out to the entire world. At the time, I did not believe I was ready to submit a piece to the legendary Transition, I merely wanted to rid my mouth of the lingering bitterness by exposing myself to greater unpleasantness ala M.K.O. Abiola. After some months, Professor Irele wrote back saying Transition had accepted my essay which it would be including in its production schedule. I simply could not believe it. I pleaded with him that I had a much better essay I would like to offer as a substitute but he was adamant about publishing the viciously scorned essay. Again, without exactly forcing it or perhaps even knowing it, Abiola Irele had taught me a few important lessons. Amongst them are the multiplicity of the forms and movement of subjectivity, the contingency and shifting loci of context, the indeterminacy and mobility of perspective and the necessity and imperative of endurance. These were lessons I would re-learn under an arguably more elaborate and structured tutelage working with Yai. Today, that initially rejected essay is one of my most cited works. Yai’s “Theory and Practice in African Philosophy: The Poverty of Speculative Philosophy”, first published in the University of Ife’s (now Obafemi Awolowo University) Second Order in 1977, stands as my introduction to a slim but extremely powerful oeuvre. I still read it until today for its contorted and multivalent magnificence. It has the effect of the sensory dissonance caused by a crack of lightning. It always seems like an unexpected electrical charge aimed at the unsuspecting heart and brain. Ideologically speaking, in that landmark essay, Yai located his existential and theoretical moorings and these could be reduced – albeit obliquely – to the following themes: a valorisation of African indigenous knowledge systems, a repudiation of intellectual elitism, a leftist epistemological orientation, and an irreverence towards complacent intellectual heroes. I was immediately enthralled by the sudden intellectual bolt of lightning that prided unevenness, roughness and dissonance as prized conceptual virtues. Yet, these unusual attributes are never placed above sound epistemological logic; a logic that is invariably deployed to validate African traditional values and epistemic regimes. At Ibadan, where I had studied, Yai’s conceptual novelties weren’t really taught and the approach there was altogether different been more or less beholden to Kwasi Wiredu’s highly influential insights. Yai’s work would have seemed too controversial, too conceptually volatile and rather undomesticated in a context that valued ‘clarity’ and ‘conceptual rigour’. Even Paulin Hountondji’s scientism and espousal of philosophy’s avowed universalism had trouble gaining acceptance at the Ibadan school of philosophy and was kept at arm’s length although there was mild suspicion that there might be some merit in his approach. Yai’s counter-paradigmatic thought and vision could simply have found no place within the comparatively staid Ibadan school. And so, the metaphor of a bolt of lightning that I adopted in relation to the first time I experienced Yai’s work seems totally appropriate. In order to experience the effect and revelation of counter-paradigmatic work, I had to grapple with texts such as Richard Rorty’s Philosophy and the Mirror of Nature when a much closer and eventually more useful proposition had been nearby at Ife, Yai’s major base. As a whole, Ife was highly suspect to the Ibadan crowd and the closest the latter got to the former was through the writings of Barry Hallen and J.O. Sodipo, particularly in works like Knowledge, Belief and Witchcraft: Analytic Experiments in African Philosophy, which nonetheless could not be regarded without a bit of tongue-in-cheek intellectual curiosity laced with lavish bemusement. Even within that specific academic context (Ife), Yai’s “Theory and Practice of African Philosophy” stood apart in engaging Hegel, Marx, Gramsci, Hountondji and Wande Abimbola all in the same breath. In so doing, he provided an intellectual tenor that was undoubtedly quite distinct within the highly idiosyncratic Ife school. It also exhibited an eclecticism that remained with Yai until the end of his days. Indeed just as Irele, Yai’s eclecticism and cosmopolitanism were never in doubt. He had studied European languages at the prestigious Sorbonne in France like his equally globally accomplished compatriot, Paulin J. Hountondji, who became his intellectual sparring partner. There had been tremendous pressure mounted by the French authorities for Yai to stick with learning and teaching the French language and linguistics, which would probably have advanced his career considerably. Instead, after the completion of his studies, he chose to return to West Africa, the University of Ibadan specifically, to specialise in Yoruba linguistics. He also taught at other universities, including Ife, Benin and the University of Florida where he retired as an emeritus professor. He compiled a dictionary in Yoruba, composed well-regarded essays on world philosophy, art and culture and then went on to serve as Benin Republic’s Permanent Delegate to UNESCO in Paris. He also subsequently served as chairperson of the organisation’s executive board. I first worked with Professor Yai when he contacted me half a decade ago to participate in the ‘epistemological forum’ of the UNESCO General History of Africa, volume IX, project, which he managed along with Martial Ze Belinga of Cameroon as co-coordinator. As for me, I embarked upon another journey of intellection and enlightenment. Even the manner he had approached me was a masterclass of an introduction all by itself. I had initially been made to understand I would be working on the illustrious Ghanaian philosopher, Kwasi Wiredu, on whom I had already written a book. I had merely thought I would be engaging in a rehash of the old ideas I had explored in my book. How wrong was I! Yai expertly nudged me in a direction I was least expecting but one that has proved to be exceedingly crucial. Yai was interested in African philosophical concepts; concepts that had been occluded and derided by trappings of modernity as well as colonialism and its numerous agents. In embarking upon this necessary journey, Yai had empowered me ideologically and conceptually. He also did so with stringent standards and utmost rigour. He made me write my paper at least six times without my realising it. The great teacher and master that he was, he never made you feel the drudgery of work and its untold frustrations; rather, each time I had to re-write the draft, it seemed like a necessary and vital initiation into ever more refined and recondite chambers of knowledge. Yai was a master and repository of arcane knowledge and with the right amount of patience, one was ushered onto horizons replete with enormous epistemic wealth and also a cultural inheritance that seemed almost limitless with possibilities. No other editor had ever made me go through at least six drafts of an essay and managed to make it such a rich and rewarding experience. It seems almost miraculous to me now when I think of how I had embarked on a journey that led to the culmination and realisation of my latent ideological inclinations as well as my intellectual intuitions without having an inkling as to what was to happen. During the Covid-19 pandemic period of 2020, we had discussions on several topics frequently by phone: Cheikh Anta Diop, Abiola Irele, Wole Soyinka, Mahatma Gandhi, and of course, Paulin Hountondji. We talked about the places of these authors and thinkers in African intellectual history and world culture. I experienced a mild kind of shock the first time I heard his voice. Sturdy in physical stature, he looked every bit an important Yoruba personage; in most circumstances, he would have been considered a traditional chieftain who was well respected in the community, but this didn’t come across in his voice; keening, ferreting, as if seeking nuggets of wisdom it might have missed previously in its haste. Or perhaps the wear and tear of teaching a highly tonal African language (Yoruba) to “tone deaf American students” had taken their toll. I remember he had to have a surgical procedure on his vocal chords which might have affected the solidity and original timbre of his voice. But one quality I never failed to notice in him was a consistent intellectual curiosity and an implacable zest for life. And the end, when it came, seemed as quick, swift and irreversible as an eagle’s majestic descent. Before then, he had asked me when I was coming to Cotonou to experience the colourful festival that celebrates Benin’s remarkable cultural and spiritual heritage during the month of January. I had been making plans to earmark the funds for such a trip. We discussed the plans in long conversations between 2 am and 5 am. I never got the impression that his health was ailing. And then suddenly he began to complain about lower back ache. We discussed about various kinds of agbo (herbal potions). And then he stopped answering my Whatsapp messages, which left me deeply worried. Finally, the news of his passing reached me. My deepest regret is that I wasn’t able to visit the master at the next edition of the Benin heritage and spiritual festival. I would miss our discussions on the differences and similarities between Vodun and Ifa, conversations about cultural authenticity and doubtful cultural assimilation and such matters. Perhaps even more than his great friend Abiola Irele, he exhibited no airs or ego when dispensing gems of arcane knowledge. Indeed, an iroko has gone on to join the ancestors. Yai’s last major paper, “Understanding Africa: African Perspectives and Epistemological Considerations”, which he delivered under the auspices of the India International Centre before the pandemic struck, revisits his central intellectual concerns. Typically, he begins by explaining the role of Yoruba women poets called yungba. These women in spite of operating in a solely monarchical context are, nonetheless, unfailingly compelled to speak truth to power regardless of whose ox is gored. Yai, in turn, pledges to assume this role of speaking the truth about less than par African governments since the dawn of independence. He then proceeds to introduce and lend validation to another concept, Global Africa, which enables him to broaden the discursive scope of his paper by drawing examples from Asia, Latin America, the Caribbean and Africa. Such a transcontinental perspective necessitates a re-consideration of the ancient Egyptian hieroglyphic texts, Kurukan Fuga, Ker Issa, Ifa, the Ubuntu texts, the Mvet inter alia. In this manner, he is able to establish transcontinental continuities that affirm the African presence in a positive cultural and epistemological light. Indeed one of the major hallmarks of Yai’s scholarship is the recuperation and validation of suppressed African knowledge systems. Before the term indigenous knowledge systems (IKS) became fashionable, he was already engaged in the field, outlining its theoretical possibilities and laying down its lexical properties. And because of his knowledge of, and familiarity with, philosophical discourse and traditions – both ancient and modern – there was nothing forced or artificial about his approach, which is a far cry from the desperate instrumentalist streak of the ‘professional’ advocates of IKS. In any given area of discourse or research, Yai was always able to locate the appropriate concepts and theories and their inevitable historicity in a reasoned and effective fashion. Conceptually and theoretically, Yai may never have attained the ragged heights of “Theory and Practice of African Philosophy” but arguably what was lost on that score was recouped in greater compactness of conceptual vision, refinements in theory and language and ultimately, greater psychic symmetry which seemed to reflect more contentment with himself, life generally, and his work. And yet we ought to remember that philosophy was merely one of the disciplines he mastered amongst others with languages, linguistics, cultural studies, art history and criticism as his major specialties. At the very beginning, a transdisciplinary tendency was already evident and this trend merely deepened as his career progressed. In addition, it lent his scholarship a polymathy that is both immensely refreshing as well as transgressive, even though it wasn’t exactly meant to be faddish. Indeed there is nothing modish about re-discovering the humbling mysteries of Ifa and its almost infinite range and possibilities. Instead the protean dimensions of such an esteemed divination system required an unforgiving and enervating quest to return to the basics which, in fact, is never basic. At every opportunity he got, Yai let it be known that he began his training and search for knowledge at the feet of village elders and sages. And this training, he never failed to point out, was every bit as significant as his Sorbonne education. In this regard, his epistemological range and flexibility, and his multicultural and multilingual endowments were simply remarkable. He had acquired an immense amount of knowledge about EuroAmerican cultures but this was never done at the expense of his indigenous Yoruba culture and its allied and accompanying formations. He was also versed in the texts of Lusophone and Afro-Brazilian cultures and traditions which he was able to interrogate at the global level before eventually linking them up with their original African roots. Vodun and Ifa are also indisputably part of our rich cultural mosaic and ought to be preserved and honoured as cornerstones of our collective heritage. Yai’s life and scholarship reflected this daunting challenge and responsibility in every word that he spoke and every word he wrote.